Peningkatan Keaktifan dan Hasil Belajar PPKn Menggunakan Model Pembelajaran Debat - Lusia Krisna Epi Iswanti (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2023)
The achievement of learning outcomes in Civics subjects at SMKN I Pleret Bantul has not been achieved. Student activity and interest in learning is still low. The purpose of this research was to find out the effectiveness of the debate model learning in an effort to increase student activity and learning outcomes. As a classroom action research, this research includes two cycles. Each cycle begins with the planning stage, then the action is carried out, and there is observation or observation, and ends with reflection. This study took the subjects of class XI TBSM A SMK N 1 Pleret Bantul for the 2019/2020 academic year, using test and observation techniques. The results showed an increase in student activity, seen from the percentage of attitudes and skills aspects. The percentage of students' attitude aspects in cycle I was 66.07% and in cycle II was 76.62%. The percentage of skill aspects in the first cycle was 69.44% and in the second cycle was 76.13%. The learning outcomes obtained by students also increased with the percentage of learning completeness starting with the pre-cycle of 53.57%, in the first cycle the percentage was obtained at 71.43%, and the second cycle was 78.57%. The success criteria have been fulfilled, namely 75%. The use of the debate model can increase understanding of learning material, increase student activity so that students are in the learning process, and can improve student learning outcomes. Besides that, it can also increase teacher creativity in using learning models so that it is more interesting and fun.